FOXP1inhibits cell growth and attenuates tumorigenicity of neuroblastoma - Ackermann, Sandra; Ehemann, Volker (BMC cancer, 2014)
Background: Segmental genomic copy number alterations, such as loss of 11q or 3p and gain of 17q, are well established markers of poor outcome in neuroblastoma, and have been suggested to comprise tumor suppressor genes or oncogenes, respectively. The gene forkhead box P1 (FOXP1) maps to chromosome 3p14.1, a tumor suppressor locus deleted in many human cancers including neuroblastoma. FoxP1 belongs to a family of winged-helix transcription factors that are involved in processes of cellular proliferation, differentiation and neoplastic transformation. - Methods: Microarray expression profiles of 476 neuroblastoma specimens were generated and genes differentially expressed between favorable and unfavorable neuroblastoma were identified. FOXP1 expression was correlated to clinical markers and patient outcome. To determine whether hypermethylation is involved in silencing of FOXP1, methylation analysis of the 5′ region of FOXP1 in 47 neuroblastomas was performed. Furthermore, FOXP1 was re-expressed in three neuroblastoma cell lines to study the effect of FOXP1 on growth characteristics of neuroblastoma cells. - Results: Low expression of FOXP1 is associated with markers of unfavorable prognosis like stage 4, age >18 months and MYCN amplification and unfavorable gene expression-based classification (P < 0.001 each). Moreover, FOXP1 expression predicts patient outcome accurately and independently from well-established prognostic markers. Array-based CGH analysis of 159 neuroblastomas revealed that heterozygous loss of the FOXP1 locus was a rare event (n = 4), but if present, was associated with low FOXP1 expression. By contrast, DNA methylation analysis in 47 neuroblastomas indicated that hypermethylation is not regularly involved in FOXP1 gene silencing. Re-expression of FoxP1 significantly impaired cell proliferation, viability and colony formation in soft agar. Furthermore, induction of FOXP1 expression led to cell cycle arrest and apoptotic cell death of neuroblastoma cells. - Conclusions: Our results suggest that down-regulation of FOXP1 expression is a common event in high-risk neuroblastoma pathogenesis and may contribute to tumor progression and unfavorable patient outcome.
Gesehen am 04.08.2020